Letramento científico através da abordagem ctsa para um curso de pedagogia - Santiago, Debora Dalila da Silva Almeida (Universidade Federal Rural do Semi-Árido, 2020)
We recognize, in this research, the need to reflect and work on inssues involving the teaching of Science, looking for new teaching approaches that make scientific literacy possible. It is important to work on questions related to scientific literacy since the early years of school life, in which the teaching and learning process happens via a teacher with a degree in Pedagogy. For that reason, it is necessary that the early education of the pedagogue approaches the formation towards the teaching of Science, sensitve and attentive to socioenvironmental questions and values. We recognize the importance of training these education professionals in the various educational levels that are of their responsibility. It is worth highlighting that, in order to be able to teach other individuals Science, one must first understand it. Thinking of this need to prepare pedagogues to promote scientific literacy, the present work aims to analyze the contributions and limitations of a Potentially Significative Teaching Unit - UEPS, for scientific literacy of Pedagogy students. At first, we performed a documentary research, in order to identify possibilities of scientific literacy in the Pedagogy program curriculum at UERN, to identify which classes would make possible the approach of the theme in question. We analyzed the the course cirriculum found in the Pedagogy PPC, where we identified 47 mandatory units, which are distributed along 8 semesters. Among those 47 units, we found 7 that approach in their curricula themes that can significantly contribute to the scientific literacy of the Pedagogy students. Later, we analyzed the attitudes and beliefs of the students about Science; for that, we used two data collection instruments: TOSLS elaborated by Cara Gormally, Peggy Brickman and Mary Lutz, which is already widely used to measure skills and abilities of scientific literacy; and a Likert scale, elaborated by the author in order to understand the students' vision on the relationship between science, technology, society and environment (STSE). Despite the difficulties in using the scientific literacy skills on TOSLS, the students showed good results on the Likert scale, in which we noticed a cricial vision about the STSE relations. Lastly, we created, based on Moreira (2011), a UEPS to promote scientific literacy with STSE approach, we applied it to the students and then evaluated the application. The students' opinions demonstrated that the UEPS was significant in the academic education process, as well as in their personal growth process. By understanding and developing their scientific literacy skills, the students became more critical and automonous regarding the dissemination of scientific information, and how it influences the decision making that directly or indirectly affects society and the environment. This process positively contributed for a citizenship formation
Keywords: Formação de professores; Letramento científico; Abordagem CTSA; Pedagogia; Teacher education; Scientific literacy; STSE approach; Pedagogy; MULTIDISCIPLINAR::ENSINO